Current applications and limitations of surgical treatments for movement disorders. Issue 1 (January 2017) - Krack, Paul; Martinez‐Fernandez, Raul; del Alamo, Marta; Obeso, Jose A.
ABSTRACT: Functional neurosurgery for the treatment of both psychiatric and neurological disorders has been performed regularly since the 1940s. However, misuse in the early days and the appearance of effective medical treatments, such as levodopa and neuroleptic drugs, greatly reduced surgical approaches over several decades. The development of a comprehensive model of basal ganglia pathophysiology in the 1990s facilitated the resurgence of functional neurosurgery, mainly for the treatment of levodopa‐related motor complications in Parkinson's disease. This led first to the re‐emergence of posteroventral pallidotomy and subsequently to deep brain stimulation. Thirty years on from this turning point, we find ourselves looking at a new scenario. Although deep brain stimulation is accepted worldwide and technical advances continue to improve this therapy, new questions and challenges such as long‐term benefits and optimal targeting have emerged. In addition, new nonincisional tools used to perform ablative treatments, such as high‐intensity focused ultrasound and gamma‐knife, are challenging classical reluctance to therapeutic lesioning, and it remains to be determined how these approaches will fit into the array of movement disorder treatments. This review discusses the current clinical state of the art of functional neurosurgery in the treatment of Parkinson's disease, tremor, and dystonia. © 2017 International Parkinson and Movement Disorder Society